Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1103/physrevc.84.014317
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic mean-field study of the properties ofZ=117nuclei and the decay chains of the293,294117 isotopes

Abstract: We have calculated the binding energy, root-mean-square radius and quadrupole deformation parameter for the recently synthesized superheavy element Z=117, using the axially deformed relativistic mean field (RMF) model. The calculation is extended to various isotopes of Z=117 element, strarting from A=286 till A=310. We predict almost spherical structures in the ground state for almost all the isotopes. A shape transition appears at about A=292 from prolate to a oblate shape structures of Z=117 nucleus in our m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 50 publications
1
59
0
Order By: Relevance
“…It is worth mentioning that the interaction parameters are able to describe the bulk properties of the nuclei reasonably good from the β-stable region to the drip-line [35,38,42,[44][45][46][47]. To deal with the open-shell nuclei, one has to consider the pairing correlations in their ground as well as excited states [33,35,38,42,[44][45][46][47]. The constant gap BCS approach is adopted for the present study and more details of the paring can be found in Ref.…”
mentioning
confidence: 99%
“…It is worth mentioning that the interaction parameters are able to describe the bulk properties of the nuclei reasonably good from the β-stable region to the drip-line [35,38,42,[44][45][46][47]. To deal with the open-shell nuclei, one has to consider the pairing correlations in their ground as well as excited states [33,35,38,42,[44][45][46][47]. The constant gap BCS approach is adopted for the present study and more details of the paring can be found in Ref.…”
mentioning
confidence: 99%
“…The mean BE is a fundamental quantity to measure the stability of nuclei and can serve as a good interior to classify superheavy nuclei by their stabilities [35]. From the droplet mass formula [36], (16) the mean binding energies are calculated using the parameter values of Moller et al [37] with r o = 1.6 fm, α 1 = 16.279 MeV, α 2 = 23 MeV, Q = 29.4 MeV, and J = 32.5 MeV, and are tabulated in Table 1 with RMF(NL3) calculations [38] and FRDM [16] results for comparison. The deviation in mean BE with FRDM [16] are due to minor parametric difference from ref.…”
Section: Resultsmentioning
confidence: 99%
“…The RMF model [18][19][20][21][22][23][24][25][26][27] al become famous in recent years and has been applied to finite nuclei and infinite nuclear matter. We have taken the RMF Lagrangian with NL3 force parameter 28 in the present study.…”
Section: The Rmf Formalismmentioning
confidence: 99%